Missed nursing care and related factors during Covid-19 pandemic: A study in southeast Iran - Rahimeh Khajoei; Mohadeseh Balvardi; Mansooreh Azzizadeh Forouzi (International Journal of Africa Nursing Sciences, 2023)
Background: Worldwide, Coronavirus Disease (COVID-19) is currently the most significant health issue. Nurses, as key members of the health care team, play a crucial role in the recovery and treatment of these patients. Quality of nursing care determines the most desirable health outcomes. The present study aimed to determine missed nursing care and related factors in COVID-19 patients. Methods: Two hundred and one nurses participated in this descriptive cross-sectional study. Questionnaires on missed nursing care for COVID-19 patients and its related factors were used to collect data. Data were collected from July 10 to September 10, 2020 and were analyzed using descriptive and analytical statistics (independent t-test, Mann Whitney, One-Way ANOVA and Kruskal Wallis test) by SPSS V.19. Results: The mean (SD) missed nursing care and its related factors were (22.99 ± 5.52), (64.84 ± 10.42) respectively, which means that cares were missed at a low level. Most of the missed cares were related to placing suspected patients in negative pressure ventilation room 12 (6 %). Physical fatigue was the most important factor contributing to missed care among 159 staff members (79.1 %). Conclusion:  Regular monitoring strategies can be decreased MNC. More studies regarding the outcomes of missed nursing care are recommended.